2018
DOI: 10.1051/shsconf/20184200058
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conceptual Change Model in the Senior High School Students’ Understanding and Character in Learning Physics

Abstract: Abstract. Learning physics for senior high school (SMA) students is often coloured by misconceptions that hinder students in achieving deep understanding. So a relevant learning model is needed. This study aims to examine the effect of conceptual change model (CCM) compared with direct instruction model (DIM) on the students' conceptual understanding and character in the subject area of motion and force. This quasiexperimental research using a non-equivalence pre-test post-test control groups design. The popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 3 publications
2
14
0
1
Order By: Relevance
“…Some of the studies shown that misconceptions still exist although had been revealed overtimes (Halim, Yong, Subahan, & Meerah, 2014;Santyasa, Warpala, & Tegeh, 2018). Some factors could be suspected as the cause of misconception, namely the learning process, curriculum, and teacher's paradigm that learning is the transfer of knowledge (Kurniawan, 2018b;Santyasa et al, 2018;Üce & Ceyhan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies shown that misconceptions still exist although had been revealed overtimes (Halim, Yong, Subahan, & Meerah, 2014;Santyasa, Warpala, & Tegeh, 2018). Some factors could be suspected as the cause of misconception, namely the learning process, curriculum, and teacher's paradigm that learning is the transfer of knowledge (Kurniawan, 2018b;Santyasa et al, 2018;Üce & Ceyhan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Model pembelajaran dengan conceptual change efektif dalam meremidiasi miskonsepsi siswa dibuktikan terjadinya perubahan konsepsi siswa dari miskonsepsi menjadi tahu konsep (Nikmah & Suyono, 2015;Sari & Nasrudin, 2015). Ditemukan dalam banyak penelitian bahwa model conceptual change memiliki dampak yang positif terhadap siswa yaitu siswa dapat mengalami pergeseran dari miskonsepsi menjadi tahu konsep (Coştu et al, 2007;Muallifah et al, 2017;Santyasa et al, 2018).…”
Section: Pendahuluanunclassified
“…Students gain a lot of knowledge in class activities designed to improve students' ability to memorize information, but they would not look for evidence themselves, rather than just sitting for the teacher's communication of ideas, so knowledge is not implemented in everyday life and will be forgotten even faster [1][2]. If rote learning and procedural skills are not practiced, knowledge gained through deep understanding may be overlooked [3][4].…”
Section: Introductionmentioning
confidence: 99%